2000
DOI: 10.1121/1.428323
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pitch-shift velocity on voice F0 responses

Abstract: Previous studies have shown that voice fundamental frequency (F0) is modified by changes in the pitch of vocal feedback and have demonstrated that the audio-vocal control system has both open- and closed-loop control properties. However, the extent to which this system operates in closed-loop fashion may have been underestimated in previous work. Because the step-type stimuli used were very rapid, and people are physically unable to change their voice F0 as rapidly as the stimuli, feedback responses might have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
107
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(117 citation statements)
references
References 7 publications
10
107
0
Order By: Relevance
“…Research involving online voice perturbation and FF shifting has shown that people tend to compensate for a change of FF in the realtime auditory feedback during vocal production, either by shifting their FF in the direction of the feedback signal (19,20) or in the opposite direction (20,38,39). The participants in our experiment in the sync condition tended to follow the stimulus rather than compensate for it in the opposite direction.…”
Section: Discussionmentioning
confidence: 74%
“…Research involving online voice perturbation and FF shifting has shown that people tend to compensate for a change of FF in the realtime auditory feedback during vocal production, either by shifting their FF in the direction of the feedback signal (19,20) or in the opposite direction (20,38,39). The participants in our experiment in the sync condition tended to follow the stimulus rather than compensate for it in the opposite direction.…”
Section: Discussionmentioning
confidence: 74%
“…The authors proposed that intonation patterns "appeared to be programmed into the speech production system at a "high level" independent of peripheral monitoring" (Mallard et al, 1978). The pitch shift studies by Larson and coworkers (Burnett et al, 1998;Larson et al, 2000) suggest than even when intonation patterns are pre-programmed, a perturbation in auditory feedback can have an immediate effect on pitch control presumably via changes in laryngeal muscle activity. It remains to be seen to what degree perturbations affecting mucosal sensation can alter laryngeal control in humans.…”
Section: The Role Of Sensory Feedback In Laryngeal Controlmentioning
confidence: 99%
“…For humans, at least, there is additional evidence that there are real-time contributions of auditory feedback to the control of ongoing vocal production. This has been demonstrated by various perturbations of auditory feedback that elicit disruptions of ongoing speech (Lee, 1950;Elman, 1981;Howell and Archer, 1984;Houde and Jordan, 1998;Larson et al, 2000). For example, exposure to delayed auditory feedback results in speech abnormalities including missequencing of syllables and slowing of speech (Lee, 1950;Howell and Archer, 1984).…”
Section: Introductionmentioning
confidence: 99%